Foreign market knowledge, international opportunity recognition, and the performance of export‐manufacturing firms. (19th January 2022) - Mostafiz, Md Imtiaz; Sambasivan, Murali; Goh, See Kwong
Abstract: Accumulating foreign market knowledge is critically essential for international entrepreneurs operating in the export‐manufacturing industry to recognise new international opportunities. Foreign market knowledge positively improves the international opportunity recognition process to achieve superior performance of export‐manufacturing firms. Foreign institutional knowledge is the most important among three types of foreign market knowledge that international entrepreneurs should leverage to recognise new opportunities. International entrepreneurs must seek foreign market knowledge from the breadth of various sources in their quest for successful international performance.